Characteristic Sonographic and Follow Up Features of Thyroid Nodules According to Childhood Age Groups - Bo Da Nam; Yun-Woo Chang; Seong Sook Hong; Ji-Young Hwang; Hyun Kyung Lim; Jeong Ho Lee; Dong Hwan Lee (대한영상의학회지, 2016)
Purpose We analyzed the spectrum and the significance of pediatric thyroid nodules depicted on sonography and evaluated the follow-up change according to the age group.